Awareness on energy conservation: a case study of first-year undergraduate students in Malaysia - Jamaludin, Adi Ainurzaman; Zulkifli, Nurul Emy Idayu; Bharin, Saherra; Jani, Rohana; Mokhtar, Mohd Istajib; Abdul Halim Lim, Sarina; Wan Mohtar, Wan Abd Al Qadr Imad; Zul Ilham (Emerald Publishing Limited, 2022)
Purpose: This paper aims to evaluate the awareness level of university students on energy conservation by focusing on their knowledge, attitude and practice. Energy awareness is a feasible energy conservation measure, but an inappropriate approach can cause the wastage of resources. The current number of reported awareness studies especially among the university student is quite limited, and focus is more given to the awareness on renewable energy, instead of energy conservation. Design/methodology/approach: A paper-based survey using a set of questionnaires that involved 2,857 respondents. There are four sections in this questionnaire, which are basic background information of respondents, knowledge (yes/true or no/false choice of responses), attitude (a scale of 1–10, where 10 indicates “strongly agree” and 1 chooses “strongly disagree”) and practices (a scale of 1–10, where 10 indicates “Always” and 1 selects “Never”). The evaluation includes the correlation analysis of all awareness variables with an educational background to disclose the most critical aspects that should be highly considered in the forthcoming awareness campaign. Findings: This research revealed that university students have a high level of awareness of energy conservation. They hold a high knowledge level and show a positive attitude with very good energy conservation practices. However, some issues require serious attention in preparing energy management plans. Effective approaches should be taken by considering the field of study, gender and family economic status to enhance the awareness level of the university students on energy conservation. Originality/value: The absence of appropriate references complicates the preparation of energy management plans including the establishment of energy policy and strategies. The findings of this research can contribute some contextual information in the local perspective to ensure the effectiveness of the energy management program and strengthen academic leadership by emphasising the element of sustainability. This is crucial for developing an energy saving culture among the young generation that will be our future scholars and leaders.